2016
DOI: 10.1002/aoc.3554
|View full text |Cite
|
Sign up to set email alerts
|

Mn(III)‐salan/graphene oxide/magnetite nanocomposite as a highly selective catalyst for aerobic epoxidation of olefins

Abstract: A nanocomposite was synthesized using carbon-coated Fe 3 O 4 nanoparticle-decorated reduced graphene oxide as a convenient and efficient supporting material for grafting of a manganese-reduced Schiff base (salan) complex via covalent attachment. The nanocomposite was characterized using X-ray diffraction, Fourier transform infrared and diffuse reflectance UV-visible spectroscopies, inductively coupled plasma atomic emission spectrometry and scanning electron microscopy. It was evaluated as a catalyst for the a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 65 publications
0
7
0
Order By: Relevance
“…The rough spherical surfaces of both HPHI ( Figure 4b) and DCHI (Figure 4c) confirm the higher capability of DCHI to embed more magnetite inside the sphere or on their surfaces more than HPHI [34]. This was attributed to greater pi interactions of olefinic and phenyl groups of DCHI ( Figure 4c) with magnetite NPs [35]. HR-TEM micrographs of HPHI-Fe 3 O 4 ( Figure 5a) and DCHI-Fe 3 O 4 (Figure 5b) confirm that the magnetite NPs were dispersed inside spherical morphologies.…”
Section: Characterization Of Hphi Dchi and Their Fe 3 O 4 Npsmentioning
confidence: 74%
“…The rough spherical surfaces of both HPHI ( Figure 4b) and DCHI (Figure 4c) confirm the higher capability of DCHI to embed more magnetite inside the sphere or on their surfaces more than HPHI [34]. This was attributed to greater pi interactions of olefinic and phenyl groups of DCHI ( Figure 4c) with magnetite NPs [35]. HR-TEM micrographs of HPHI-Fe 3 O 4 ( Figure 5a) and DCHI-Fe 3 O 4 (Figure 5b) confirm that the magnetite NPs were dispersed inside spherical morphologies.…”
Section: Characterization Of Hphi Dchi and Their Fe 3 O 4 Npsmentioning
confidence: 74%
“…The catalytic activity and yield of epoxides on the nanocomposite catalyst under the optimized conditions was investigated . There was no distinct effect of the steric properties on the reactivity of the olefins.…”
Section: Synthesis and Application Of Graphene‐based Catalystsmentioning
confidence: 99%
“…There was no distinct effect of the steric properties on the reactivity of the olefins. The epoxide yield is enhanced with increasing nucleophilicity of the olefin . We studied the epoxidation of various substrates over various kinds of catalysts (VO IV T, VO IV G, MoO 2 VI T, and MoO 2 VI G), and found that the conversion of different substrates followed the order geraniol>cyclooctene>styrene>1‐octene, which was related to electron density and hindrance effects.…”
Section: Synthesis and Application Of Graphene‐based Catalystsmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, two major side reactions, allylic oxidation and epoxide ring‐opening, can considerably occur in epoxidation of cyclohexene, resulting in cyclohexene epoxidation to epoxide becoming difficult . Great efforts have been made in the development of new active and selective catalysts for cyclohexene/olefins epoxidation to circumvent the above‐mentioned side reactions and facilitate the formation of the desired product …”
Section: Introductionmentioning
confidence: 99%